Pengembangan Literasi Digital di Dayah Perbatasan - Maha, Mahadi; Fatiya, Namiya (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2024)
Abstract: The research aims to analyze and find a model of digital literacy development in Islamic boarding schools. The research uses a qualitative paradigm with descriptive survey techniques. Data were obtained from interview results, documentation, and observation. The data were then processed with reduction techniques and analyzed using data triangulation. The study's findings indicate that the digital literacy development carried out by Dayah Perbatasan Darul Amin focuses on the understanding of students and teachers, both implicitly and explicitly. Attention is also directed towards the formation of an information ecosystem in the boarding school related to software (ethics and morals) and hardware (improvement of facilities and infrastructure). The development of literacy is also carried out through the establishment of the boarding school's organizational culture and the expansion of cooperation. Abstrak: Penelitian bertujuan untuk menganalisis dan menemukan sebuah model pengembangan literasi digital di pesantren. Penelitian menggunakan paradigma kualitatif dengan teknik survei deskriptif. Data diperoleh dari hasil wawancara dokumentasi dan observasi. Data kemudian diolah dengan teknik reduksi dan dianalisis menggunakan triangulasi data. Hasil penelitian menunjukkan Pengembangan literasi digital yang dilaksanakan oleh Dayah Perbatasan Darul Amin terfokus kepada pemahaman literasi santri dan guru baik secara implisit maupun eksplisit. Perhatian juga mengarah kepada pembentukan ekosistem informasi di dayah berkaitan dengan software (etika dan moral) dan hardware (peningkatan sarana prasarana). Pengembangan literasi juga dilaksanakan melalui pembentukan budaya organisasi pesantren dan perluasan kerjasama.